2020
DOI: 10.1785/0220200009
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Palu Tsunami: Coeval Landslide and Coseismic Sources

Abstract: On 28 September 2018, Indonesia was struck by an MW 7.5 strike-slip earthquake. An unexpected tsunami followed, inundating nearby coastlines leading to extensive damage. Given the traditionally non-tsunamigenic mechanism, it is important to ascertain if the source of the tsunami is indeed from coseismic deformation, or something else, such as shaking induced landsliding. Here we determine the leading cause of the tsunami is a complex combination of both. We constrain the coseismic slip from the earthquake usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Bao et al (13) and Socquet et al (14) were among the first to recognize the supershear nature of this earthquake (13,14). Several authors (13,(15)(16)(17) have postulated that submarine landslides, triggered by the earthquake's strong ground motion, were the primary source for the devastating tsunami. Ulrich et al (18) argued that the earthquake displacements were critical to the tsunami generation.…”
mentioning
confidence: 99%
“…Bao et al (13) and Socquet et al (14) were among the first to recognize the supershear nature of this earthquake (13,14). Several authors (13,(15)(16)(17) have postulated that submarine landslides, triggered by the earthquake's strong ground motion, were the primary source for the devastating tsunami. Ulrich et al (18) argued that the earthquake displacements were critical to the tsunami generation.…”
mentioning
confidence: 99%
“…The Palu earthquake unexpectedly generated multiple tsunamis (Williamson et al, 2020) that caused severe damage and, in some cases, complete coastal inundation to low-lying settlements along Palu Bay (Fig. 7A and B).…”
Section: Tsunami Effectsmentioning
confidence: 99%
“…The question considered was whether the Palu tsunami was triggered primarily by coseismic deformation beneath Palu Bay or shaking-induced landslides. Several studies (Sepulveda et al, 2020;Williamson et al, 2020;Liu et al, 2020;Carjaval et al, 2019;Gusman et al, 2019;Ulrich et al, 2019) have suggested the answer may be a combination of the two processes.…”
Section: The Origin Of the Palu Tsunamimentioning
confidence: 99%
See 2 more Smart Citations